Phonological Analysis of Indian Language - Adiprana Yogatama (IAIN Salatiga, 2012)
The aims of this research are to find out the language sounds produced by India speakers, to enrich the scientific realm of language sounds and to stimulate the students to deeply examine other foreign language sounds. For the purpose of the study, the researcher collected data from several sources. The data which were in the form of theoretical research literature were obtained from books in general linguistics, especially on Phonology, both English and Indonesian. For data or material which were in the form of research material to be studied, the researcher presented a native speaker of Indian language named Kour Herbinder. This research is a qualitative research with recording and note technique. To analyze the data, the researcher used phonetics chart, both for cconsonants and vowels. From the analysis result, the researcher found that the sounds in India language are dominated by alveolar sounds like usually pronounced by speakers of Indonesian Balinese dialect. The researcher also found that there are many variations of Indian language sound as allophones, such as sound [k '] is an allophone of [k], and sound [dh] is an allophone of [d]. The pronunciation of sound [t], [d] and [k] dominantly resembles with [t], [d] and [k] on Indonesian Balinese.Keywords: phonetics ; phonemics ; alveolar ; allophone